2020
DOI: 10.1108/ijwhm-10-2019-0126
|View full text |Cite
|
Sign up to set email alerts
|

Boards of directors' influences on occupational health and safety: a scoping review of evidence and best practices

Abstract: PurposeTo review the literature and identify research gaps in the role and influence boards of directors of companies have in occupational health and safety (OHS).Design/methodology/approachThis was done in a scoping review built on a structured search in MEDLINE (PubMed), EMBASE, PsycINFO, Sociological Abstracts, CCInfoWeb, EconLit, Web of Science, CINAHL and gray literature. Citations and reference lists were tracked. Inclusion criteria were publication in English. Exclusion criteria were studies covering co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…, 2015; Hoque and Shahinuzzaman, 2021), their commitment (Berhan, 2020) has a significant impact on their performance and also causes a great reduction in risk and disease-causing. Again, Ebbevi et al. (2020) after a review of forty-nine studies confirmed that one set of best practices is not applicable in all context and organisation, justifying the need for this study to find out what pertains in the developing countries' context.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…, 2015; Hoque and Shahinuzzaman, 2021), their commitment (Berhan, 2020) has a significant impact on their performance and also causes a great reduction in risk and disease-causing. Again, Ebbevi et al. (2020) after a review of forty-nine studies confirmed that one set of best practices is not applicable in all context and organisation, justifying the need for this study to find out what pertains in the developing countries' context.…”
Section: Introductionmentioning
confidence: 92%
“…This is because the successful management of employees' anxiety (Aguiar-Quintana et al, 2021), health and safety (Huber et al, 2015;Hoque and Shahinuzzaman, 2021), their commitment (Berhan, 2020) has a significant impact on their performance and also causes a great reduction in risk and disease-causing. Again, Ebbevi et al (2020) after a review of forty-nine studies confirmed that one set of best practices is not applicable in all context and organisation, justifying the need for this study to find out what pertains in the developing countries' context. This is important because there exists research in developed countries that identify strategies used during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Also relevant is a small, but improving, research base on board impact on work health and safety (Ebbevi et al, 2021;Lornudd et al, 2020Lornudd et al, , 2021. That body of research has begun to identify how boards influence organisational performance in that arena.…”
Section: Ex I St I Ng Li T Er At U R Ementioning
confidence: 99%
“…Untuk menjadikan perilaku keselamatan sehingga aman dalam bekerja tidak hanya dilakukan oleh pihak perusahaan namun juga diperlukan partisipasi karyawan. Ada pemahaman yang berkembang bahwa kepemimpinan operatif mulai dari manajer lini hingga manajemen senior memainkan peran penting dalam kesehatan dan keselamatan kerja (OHS) (Ebbevi et al, 2021). Dengan adanya penerapan budaya aman secara menyeluruh maka akan secara efektif memperbaiki perilaku tidak aman karyawan sehingga timbul kubermaknaan pekerjaan (Ni et al, 2022).…”
Section: Kajian Pustaka Dan Pengembangan Hipotesisunclassified